2016
DOI: 10.1186/s12884-016-0949-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of obstetric care for women with obstructed labour in the national referral hospital in Uganda: lessons learnt from criteria based audit

Abstract: BackgroundObstructed labour remains a major cause of maternal morbidity and mortality whose complications can be reduced with improved quality of obstetric care. The objective was to assess whether criteria-based audit improves quality of obstetric care provided to women with obstructed labour in Mulago hospital, Uganda.MethodsUsing criteria-based audit, management of obstructed labour was analyzed prospectively in two audits. Six standards of care were compared. An initial audit of 180 patients was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 11 publications
3
46
0
5
Order By: Relevance
“…The review of previous studies on partograph completion, including studies done at Mulago Hospital, indicated that the rate of completion for several aspects of the partograph was below the required standard (Kayiga et al, 2016). It was therefore agreed that the standards be set lower than 100% as a more realistic expectation of the current state of care.…”
Section: Criteria and Standardsmentioning
confidence: 99%
“…The review of previous studies on partograph completion, including studies done at Mulago Hospital, indicated that the rate of completion for several aspects of the partograph was below the required standard (Kayiga et al, 2016). It was therefore agreed that the standards be set lower than 100% as a more realistic expectation of the current state of care.…”
Section: Criteria and Standardsmentioning
confidence: 99%
“…Almost three quarters of the MDs due to primary postpartum haemorrhage(PPH) and sepsis have OL as an underlying cause [4,5]. Limited or no access to quality emergency obstetric care services in low resource settings contributes to the high number of adverse obstetric outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…7In Uganda, obstructed labour is not a rare event and is sometimes diagnosed at a late stage with severe caput succedaneum and moulding. (32) This might have contributed to the misconception that caput and moulding are pathological ndings indicative of cephalo-pelvic disproportion and that CS is the only possible intervention in case these are present. Concerns about cephalo-pelvic disproportion is hence probably the reason that "Big baby" is seen as a contraindication.…”
Section: Discussionmentioning
confidence: 99%